Sports tourism : participants, policy and providers - Weed, Mike (Elsevier/Butterworth Heinemann, 2004)
Sports Tourism: participants, policy and providers is an unparalleled text that explains sports tourism as a social, economic and cultural phenomenon that stems from the unique interaction of activity, people and place. Unlike other texts, it seeks to present sports tourism as a unique area that produces its own unique issues, concerns and controversies. The text tackles these issues from three viewpoints: participants: examining the profiles, motivations and behaviour patterns of sports tourists to create a typology of participantspolicy: analyses the response by policy makers to this phenomen.